Adab Guru Dan Murid Perspektif Kh. Hasyim Asy’ari Studi Atas Kitab Adabul ‘Ālim Wal Muta’alim - kaimudin; Maulana, Alek; Abidin, Zaenal (Edusifa: Jurnal Pendidikan Islam, 2023)
This study aims to determine the etiquette of teachers and teachers contained in the book of Adab al-Alim wa al-Muta'allim by K.H. M. Hasyim Asya'ari. This research is a qualitative research with a literature review approach. K.H. M. Hasyim Asya'ari gave a clear explanation of some concepts of etiquette that need to be applied by teachers and students, so that teacher and student relationships will be created who have noble, polite manners, of course in accordance with the guidance of the Qur'an. In collecting data in this study, namely by searching, collecting, reading and analyzing books that are relevant to the research problem, then processed according to the ability of the author. The findings show that the concept of adab in learning which was initiated by K.H. M. Hasyim Asya'ari. In this, there are several concepts, including the etiquette of a teacher when teaching, or the manners of a student when studying.